The Water-Energy-Food Nexus Beyond “Technical Quick Fix”: The Case of Hydro-Development in the Blue Nile Basin, Ethiopia - Müller-Mahn, Detlef; Gebreyes, Million; Allouche, Jeremy; Debarry, Annapia (Frontiers in Water, 2022)
This paper builds upon empirical material from a case study of two dam sites in Ethiopia to revisit nexus narratives from a political ecology perspective. The two dams on tributaries of the Upper Blue Nile are examples of the success of hydro-development to increase food and energy production, but at the same time they give evidence of the controversial effects these developments have on local populations. The paper argues that conventional nexus thinking has often been too water- and economy-centric, and too much focussed on a “technical quick fix” instead of a holistic approach. The paper calls for a broadening of nexus perspectives in order to better acknowledge the social complexity of hydro-development in local contexts, to understand the political construction of scarcity, and to combine different knowledges at the science-practice interface.